The optimal degree of monetary-discretion in a New Keynesian model with private information - Yuichiro Waki; Richard J. Dennis; Ippei Fujiwara (Theoretical Economics, 2018)
This paper considers the optimal degree of monetary-discretion when the central bank conducts policy based on its private information about the state of the economy and is unable to commit. Society seeks to maximize social welfare by imposing restrictions on the central bank's actions over time, and the central bank takes these restrictions and the New Keynesian Phillips curve as constraints. By solving a dynamic mechanism design problem we find that it is optimal to grant "constrained discretion" to the central bank by imposing both upper and lower bounds on permissible inflation, and that these bounds should be set in a history-dependent way. The optimal degree of discretion varies over time with the severity of the time-inconsistency problem, and, although no discretion is optimal when the time-inconsistency problem is very severe, it is a transient phenomenon and some discretion is granted eventually.
Keywords: D82; E52; E58; 330; Rules versus discretion; monetary policy; New Keynesian model; private information; delegation; mechanism design; inflation targeting